BUDIDAYA LADA BERPINDAH: KASUS LADA BANGKA BELITUNG - Usman Daras; . Gusmaini (Perspektif, 2016)
The province of Bangka Belitung islands are producing areas of black pepper from which Muntok White Pepper wellkown over the world is produced. Unportunetely, the exported commodity is obtained through traditional agricultural system, where cultivated lands of the crop commonly move from one site to others, after 2-3 times of harversting seasons. In establishing of pepper vine orchards, farmers usually open secondary forests (forested lands) and followed by burning any dried parts of cut plants. This may result in declining of soil fertility, productivity of the crop, and its economical life as much humus and soil organic matter is burned as well. The growth of pepper vines will become worse since farmers commonly do not look after the crops properly, including added fertilizers adequately. In the future, such approach may not be maintained due to narrowed land-ownership generated by increase of population and other land use purposes. Therefore, fixed cultivation of the crops may be a single solution in growing pepper vines at Babel. In other words, the crops should be cultivated intensively by introducing proper management of the crops. Any main factors believed to be causes why farmers do so should be identified. The approach is expected to improve productivity, economical life of the crop more than 7 years) and sustainable.